2023
DOI: 10.3390/ijms24097947
|View full text |Cite
|
Sign up to set email alerts
|

Iron Saturation Drives Lactoferrin Effects on Oxidative Stress and Neurotoxicity Induced by HIV-1 Tat

Abstract: The Trans-Activator of Transcription (Tat) of Human Immunodeficiency Virus (HIV-1) is involved in virus replication and infection and can promote oxidative stress in human astroglial cells. In response, host cells activate transcription of antioxidant genes, including a subunit of System Xc− cystine/glutamate antiporter which, in turn, can trigger glutamate-mediated excitotoxicity. Here, we present data on the efficacy of bovine Lactoferrin (bLf), both in its native (Nat-bLf) and iron-saturated (Holo-bLf) form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…The protective role of Lf against pathogenic processes related to the expression of the sole viral proteins was also reported in the study by Ianiro and colleagues, where iron saturation rate was found to drive bLf effects on oxidative stress and neurotoxicity induced via HIV-1 Tat [28]. Despite tremendous advances in combined antiretroviral therapy, the standard therapy for HIV-1 infection, HIV + patients can experience HIVassociated neurocognitive disorders [29], mainly due to the chronic basal expression of HIV-1 non-structural proteins, such as Tat, which can trigger neurotoxic effects, related to both oxidative stress induction and excitotoxicity [30,31].…”
supporting
confidence: 60%
“…The protective role of Lf against pathogenic processes related to the expression of the sole viral proteins was also reported in the study by Ianiro and colleagues, where iron saturation rate was found to drive bLf effects on oxidative stress and neurotoxicity induced via HIV-1 Tat [28]. Despite tremendous advances in combined antiretroviral therapy, the standard therapy for HIV-1 infection, HIV + patients can experience HIVassociated neurocognitive disorders [29], mainly due to the chronic basal expression of HIV-1 non-structural proteins, such as Tat, which can trigger neurotoxic effects, related to both oxidative stress induction and excitotoxicity [30,31].…”
supporting
confidence: 60%
“…Apo-Lf appears to be more effective in the antioxidant response by virtue of its ability to sequester ferric ions (Fe 3+ ), thus protecting against the damaging effects of oxidative stress, specifically by limiting the production of hydroxyl radicals and peroxidized lipids [12,13]. A recent study by Ianiro and colleagues reported that the iron saturation rate influences the antioxidant and neuroprotective role of Lf in astrocytoma cells expressing the human immunodeficiency virus type 1 (HIV-1) Tat protein [14]. Bullen et al [15] showed that the antibacterial activity of Lf decreases as the level of iron saturation increases.…”
Section: Lactoferrin: General Aspectsmentioning
confidence: 99%
“…Interestingly, Lf has a unique ability to access the nucleus of cells and interact with specific and non-specific DNA sequences, functioning as a transcription factor [153,154]. It has been found to facilitate the nuclear translocation of nuclear factor erythroid-2-related factor 2 (Nrf2) [14,155], a crucial regulator of the cellular antioxidant response. Moreover, Lf contributes to the upregulation of Fpn, the sole iron exporter, thus actively contributing to reverse anemia-related sequelae [6].…”
Section: Lactoferrin and Iron Metabolismmentioning
confidence: 99%
See 2 more Smart Citations